Protein kinase C modulates mitogenic signalling by epidermal growth factor in T51B rat liver cells. - Sharma, Rakesh. (University of Ottawa (Canada), 1994)
The regulation of the proliferation of non-neoplastic T51B rat liver epitheloid cells involves a complex interplay between the epidermal growth factor (EGF) and the protein kinase C (PKC) signal-transduction pathways. T51B cells can be made proliferatively quiescent upon prolonged serum deprivation, which results in their growth-arrest at the G1 phase of the cell cycle. Addition of EGF (1.5$\eta$M) or, re-addition of serum (10% BCS) to the conditioned medium initiates DNA synthesis, within 8 hours, which reaches a maximum by 18-24 hours, when a significant number of cells are in the S phase. The DNA synthetic responses of EGF and serum are additive. Growth factor or, serum-stimulated DNA synthesis is followed by an increase in cell number. The mitogenic response of EGF can be blocked by 15-20$\mu$M genistein, a tyrosine kinase inhibitor. EGF activates particulate PKC within 15 minutes, and the stimulation reaches a maximum by 35-45 minutes. PKC activity then remains elevated for up to 24 hours. The tumour promoting phorbol ester, TPA, which is known to activate PKC, is not mitogenic to T51B cells. TPA modulates the responses of EGF or, serum depending upon the culture conditions. When TPA is added to serum-deprived cells in the presence of EGF or serum, it potentiates DNA synthesis within 18 hours, during which time it down-regulates PKC. On the other hand, if TPA is present in the medium during serum-deprivation, the response to EGF in these PKC-inactivated cells is as mitogenic as that caused by serum. However, TPA pretreatment makes the cells less responsive to EGF or serum in that, the net DNA synthesis is significantly reduced ($>$30%) in control, and in treated cells. The inhibitory response of genistein is slightly attenuated in the presence of EGF and TPA. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.